The criminalisation of homosexuality in St Kitts-Nevis: examining the rhetoric - Rowtham, Moyia (The Palgrave handbook of Caribbean criminology, 2024)
Over sixty countries bear national laws which criminalise same-sex relationships between consenting adults. The laws of St. Kitts and Nevis (SKN) do not synchronise in the argument for the criminalisation of homosexuality. This resulted in the 2022 High Court ruling which overturned the colonial-era sodomy-related law on the grounds of unconstitutionality via the contravention of fundamental rights to personal privacy and freedom of expression. The chapter examines SKN laws, including its Constitution as well as scrutinises its current positioning in relation to the criminalisation of homosexuality, while making an argument for the application of the Rule of Law, without adopting a stance on the criminal or attitudinal norms that exist.